Supportive data for "Short-term apparent mutualism drives responses of aquatic prey to increasing productivity", Chaguaceda et al. - Chaguaceda, Fernando; Scharnweber, Kristin; Dalman, Erik; Tranvik, Lars; Eklöv, Peter (Uppsala University, 2020)
Dataset related to the publication "Short-term apparent mutualism drives responses of aquatic prey to increasing productivity"

This dataset contains both biological variables (phytoplankton, periphyton, zooplankton, Chironomidae emergence) and physico-chemical variables (temperature, dissolved oxygen, pH, turbidity) of an aquatic mesocosm experiment that gradually manipulated nutrient additions (10 nutrient steps, 20 – 1000 µg L -1 total P (TP) and 0.45 – 11.3 mg L -1 total N (TN)) and also manipulated the presence or absence of generalist fish (Crucian carp, Carassius carassius), making a total of 10*2=20 mesocosms.

Crucian carp feed both on benthic prey (Chironomidae) and on pelagic prey (Cladocera). Based on that, this experiment aimed to test the indirect interactions between Chironomidae and Cladocera prey due to shared predation, and how these interactions changed in response to nutrient additions through changes in benthic and pelagic food-web pathways.

In the dataset there are five different sheets:

Sheet number 1 shows the summary values of all the variables after the fish were added. Most variables are shown as mean values over a 7-week experimental period (after fish addition).

The other sheets show the time-series of food-web variables (Phytoplankton Chla, periphyton biomass, Chironomidae emergence and Cladocera abundance), where the week refers to week relative to fish addition (week 0 is the first week after fish addition).

The dataset was originally published in DiVA and moved to SND in 2024.

Dataset related to the publication "Short-term apparent mutualism drives responses of aquatic prey to increasing productivity"

This dataset contains both biological variables (phytoplankton, periphyton, zooplankton, Chironomidae emergence) and physico-chemical variables (temperature, dissolved oxygen, pH, turbidity) of an aquatic mesocosm experiment that gradually manipulated nutrient additions (10 nutrient steps, 20 – 1000 µg L -1 total P (TP) and 0.45 – 11.3 mg L -1 total N (TN)) and also manipulated the presence or absence of generalist fish (Crucian carp, Carassius carassius), making a total of 10*2=20 mesocosms.

Crucian carp feed both on benthic prey (Chironomidae) and on pelagic prey (Cladocera). Based on that, this experiment aimed to test the indirect interactions between Chironomidae and Cladocera prey due to shared predation, and how these interactions changed in response to nutrient additions through changes in benthic and pelagic food-web pathways.

In the dataset there are five different sheets:

Sheet number 1 shows the summary values of all the variables after the fish were added. Most variables are shown as mean values over a 7-week experimental period (after fish addition).

The other sheets show the time-series of food-web variables (Phytoplankton Chla, periphyton biomass, Chironomidae emergence and Cladocera abundance), where the week refers to week relative to fish addition (week 0 is the first week after fish addition).

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supportive data for "Short-term apparent mutualism drives responses of aquatic prey to increasing productivity", Chaguaceda et al.
Keywords: ecology; ekologi; Ecology; Ekologi